Analysis of The Impact of BAZNAS Productive Zakat Investment on The Cibuluh Bogor Batik Village Program Using SROI Methods - Afia Salsabila; Farida Ratna Dewi; Eka Dasra Viana (Center of Strategic Studies (PUSKAS) BAZNAS, 2022)
Sustainable development programs have goals that are globally known as Sustainable Development Goals (SDGs). The United Nations said that there were 17 goals to be achieved in the program. One of its goals is to end all forms of poverty everywhere. The poverty rate in Indonesia has increased in 2020 due to the Covid-19 pandemic. One way that can be used to overcome these problems is to implement community empowerment programs. The Cibuluh Bogor Batik Village is a community empowerment program in the form of productive zakat activities distributed by BAZNAS. Appropriate evaluation methods are needed to measure the impact of the program on the community. Social Return on Investment (SROI) is a program evaluation tool that can be used to measure the impact of social investment generated. This study aims to analyze the program innovation and social rate of return of the Cibuluh Bogor Batik Village program. The type of data used is primary and secondary data. Data were analyzed by the SROI method. The results show that the social return value is 1,12:1, meaning that every IDR1 invested will benefit IDR1,12 for stakeholders.